Novel Expansion of Matrix Metalloproteases in the Laboratory Axolotl (Ambystoma mexicanum) and Other Salamander Species - Al Haj Baddar, Nour; Timoshevskaya, Nataliya; Smith, Jeramiah J.; Guo, Houfu; Voss, S. Randal (Frontiers in Ecology and Evolution, 2021)
Matrix metalloprotease (MMP) genes encode endopeptidases that cleave protein components of the extracellular matrix (ECM) as well as non-ECM proteins. Here we report the results of a comprehensive survey of MMPs in the laboratory axolotl and other representative salamanders. Surprisingly, 28 MMPs were identified in salamanders and 9 MMP paralogs were identified as unique to the axolotl and other salamander taxa, with several of these presenting atypical amino acid insertions not observed in other tetrapod vertebrates. Furthermore, as assessed by sequence information, all of the novel salamander MMPs are of the secreted type, rather than cell membrane anchored. This suggests that secreted type MMPs expanded uniquely within salamanders to presumably execute catalytic activities in the extracellular milieu. To facilitate future studies of salamander-specific MMPs, we annotated transcriptional information from published studies of limb and tail regeneration. Our analysis sets the stage for comparative studies to understand why MMPs expanded uniquely within salamanders.